The Analysis on the Effect of Motivation and Working Environment on Working Discipline and Employee’ Performance - Muh. Sapril Ahmad; Musran Munizu; Maat Pono (Magister Management, Hasanuddin University, 2021)
The study aims to analyze the effect of motivation and working environment on working discipline and employee’ performance at Village Administration Offices in Maros Regency. The research used the quantitative approach. The research populations were the village administration employees with the status of the State Civil Apparatus as many as 153 employees. Data were collected using observation, interview, documentation, and questionnaire. The data were analyzed using the Path Analysis with SPSS 24 program. The research result indicates that motivation, working environment affect the employees’ working discipline. Motivation and working environment affect the employees’ performance. It also found that motivation and working environment influences the employees’ performance through the working discipline of the village administration employees at Maros Regency.